Teachers' Perceptions of the Efficacy of Positive Behavior Support Systems - Herawati, Netty; Jafari, Mohammadbagher; Sanders, Karin (International Journal of Education and Cognitive Sciences, 2022)
Purpose: This study aims to explore teachers' perceptions of the efficacy of Positive Behavior Support (PBS) systems in educational settings. Methods and Materials: Employing a qualitative research design, this study conducted semi-structured interviews with 24 teachers who have experience implementing PBS in their classrooms. Participants were selected through purposive sampling to ensure a diverse range of experiences. The interviews were designed to elicit in-depth insights into teachers' perceptions of PBS, focusing on the impact on student behavior, implementation strategies, challenges, and the role of leadership. Data were analyzed thematically to identify key themes and concepts related to the efficacy of PBS. Findings: The analysis revealed six main themes: Impact of PBS on Student Behavior, Implementation Strategies, Perceived Benefits of PBS, Challenges and Barriers, Role of School Leadership, and Teacher Experiences and Perceptions. Teachers reported positive changes in student behavior, including increased engagement and reduced disruptions, as a result of implementing PBS. However, challenges such as resource limitations, the need for ongoing professional development, and the importance of school leadership support were also identified. The findings highlight the multifaceted nature of PBS implementation and its varied impacts on the educational environment. Conclusion: This study underscores the potential of PBS systems to foster positive behavioral changes and improve the educational environment. However, it also highlights the complexities involved in implementing such systems, including the need for adequate resources, continuous teacher training, and strong leadership support. Understanding teachers' perceptions provides valuable insights into the factors that contribute to the success and challenges of PBS, offering guidance for its effective implementation in schools.